ANALISIS KESESUAIAN AKAD HIWALAH DALAM PRAKTIK PEMBIAYAAN LEMBAGA KEUANGAN SYARIAH - Nurul Ainiah; Moh. Karim (Jurnal Ekonomi Syariah Darussalam, 2026)
The hiwalah contract has an important role in the sharia financial system. The development of sharia financial institutions in Indonesia makes hiwalah contracts increasingly relevant to study, considering that the need for transaction systems that are efficient and in accordance with sharia principles continues to increase. The issues in this article include the meaning of hiwalah, its legal basis in Islam, the pillars and conditions that must be met, the implementation scheme, and its application in sharia financial institutions. This research aims to analyze the concept of the hiwalah contract comprehensively from both theoretical and practical aspects. The method used is normative legal research with a literature study approach through various relevant books and scientific articles in the last ten years. The results of the study show that the hiwalah contract has a strong legal basis in the Al-Qur'an, Hadith, and Ijma' Ulama, and can be implemented in modern sharia banking practices as an instrument for transferring legal obligations. Thus, a good understanding of the hiwalah contract is important in supporting the effectiveness of transactions and maintaining compliance with sharia principles in the financial system. Kata Kunci: Profit Sharing, Hiwalah Agreements, Muamalah Fiqh